2021
DOI: 10.1096/fj.202101077r
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent contraction: The non‐classical action of endothelial prostacyclin, its underlying mechanisms, and implications

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 134 publications
(468 reference statements)
0
11
0
Order By: Relevance
“…Some studies have shown that G protein-coupled receptor activation of the cAMP pathway is involved in PGI2-induced vasoconstriction (43) (Figure 4). In addition, Rucker et al showed that PGI and thromboxane are involved in maintaining vascular autostasis (44,45). Reduced PGI levels and increased thromboxane levels were found in constricted pulmonary arteries of patients with PH-LHD.…”
Section: Pgi2 Pathwaymentioning
confidence: 99%
“…Some studies have shown that G protein-coupled receptor activation of the cAMP pathway is involved in PGI2-induced vasoconstriction (43) (Figure 4). In addition, Rucker et al showed that PGI and thromboxane are involved in maintaining vascular autostasis (44,45). Reduced PGI levels and increased thromboxane levels were found in constricted pulmonary arteries of patients with PH-LHD.…”
Section: Pgi2 Pathwaymentioning
confidence: 99%
“…PGE2/E-prostanoid 3 receptor (EP3) signaling can mediate acute inflammatory J o u r n a l P r e -p r o o f 6 responses in disease models via the EP3/Gi/Ca 2+ influx signaling pathway 32,33 . We [34][35][36][37] and others 38 have elucidated that prostaglandins besides PGE2 can also activate EP3.…”
Section: Introductionmentioning
confidence: 95%
“…No off-target sites were found in E. tenella genome with up to three nucleotides mismatch between the crRNA and potential off-target sites. Meanwhile, if there are more than two nucleotides mismatch, FnCas12a can efficiently distinguish and reject the off-target sites (Liu et al, 2021). Thus, we assume a high specificity of gene manipulation at the desired target locus.…”
Section: Fncas12a-mediated Knock-outmentioning
confidence: 99%